Bridging the Gap: The Role of Innovation in Connecting Design Thinking, Entrepreneurship Education, and Business Success - Alghizzawi, Mahmoud; Ussama Majeed, Muhammad; Hussain, Zahid; Aslam, Sumaira; Aljundi , Nawaf; Abu-AlSondos , Ibrahim A.; Ratib Ezmigna, Abd Alrahman (Data and Metadata, 2025)
Introduction: Innovation is a critical driver of business success, especially in today’s dynamic global economy. This study investigates how design thinking (DT) and entrepreneurship education (EE) impact business success (BS) in Pakistani institutions, with a focus on the mediating role of innovation. The research highlights the synergy between DT and EE in fostering environments where students can develop innovative business ideas.Methods: A systematic sampling approach was used, involving 260 students from various universities to ensure a comprehensive assessment of the impact of EE and DT on BS.  SPSS and Smart PLS was used to analyze the data.Results: The study’s findings emphasize innovation’s crucial role in linking entrepreneurship education and design thinking with business success. By identifying how innovation bridges these components, educational institutions can enhance their curricula to better equip students with entrepreneurial skillsConclusions: This research provides valuable recommendations for refining educational strategies to cultivate innovative mindsets, preparing students for the challenges of the modern business world.